Ecopedagogy Based on Preserving the Local Wisdom of Kampung Naga in Cultivating Environmental Care in Geography Education Students - Mulyanie, Erni; Rismawati, Resi; Al Husaini, Hamzah (Universitas Lambung Mangkurat, 2024)
This research discusses an eco-pedagogical approach based on preserving the local wisdom of the Kampung Naga community in cultivating a critical attitude of caring for the environment in geography education students at Siliwangi University. The research method uses a quantitative approach with data obtained through questionnaires and documentation studies. The data analysis technique used was descriptive statistics and a simple linear regression statistical test was also carried out to determine the effect of the eco-pedagogic approach on a critical attitude towards caring for the environment. The population in this study were geography students at Siliwangi University with a sample size of 40 people. The results of data analysis show that students have high levels of cultural eco-literacy and critical eco-literacy, as well as a respectful attitude towards the environment, the principle of responsibility, the principle of living simply and in harmony with nature, the principle of justice, the principle of democracy, and the principle of good moral integrity. This research also shows that the eco-pedagogic approach has a significant influence on the development of students' critical attitudes toward caring for the environment.